EVALUASI DAN IMPLIKASI KEBIJAKAN PEMERINTAH PENANGGULANGAN KEMISKINAN DI KOTA MAKASSAR - Misbahuddin Misbahuddin (AkMen JURNAL ILMIAH, 2014)
Based on the research results, it can be concluded implications and impact of poverty reduction programs undertaken by the Government of Makassar in the period 2008 - 2012 which is an increase skills (skills), improving homes, as well as increased opportunities for poor people who were subjected to program has not been felt by the public. Evalausi the implementation of poverty reduction programs undertaken by the Government of Makassar during the period of 2008 through 2012 shows that the effectiveness criteria are classified as good, relatively good efficiency criteria, adequacy criteria are classified as good and sufficient, criterion perataannya relatively poor, relatively good responsivitasnya criteria, as well as relatively good accuracy criteria.